Ethnomathematics Of Tumpeng And Banyuwangi Tumpeng Sewu Rituals As Students’ Worksheets - Faiqotul Himmah; Toto’ Bara Setiawan; Lioni Anka Monalisa; Didik Sugeng Pambudi; Dinawati Trapsilasiwi (Pancaran Pendidikan, 2019)
Mathematics is very closely related to the habits that exist in society. The habits that exist in society can be called a culture. The concept or aspect of mathematics related to culture is called ethnomathematics. Ethnomathematics can also be used as teaching materials that can attract students' interest in mathematics, because students will find it easier to learn science that is directly related to real life. Thus, ethnomathematics is very important in mathematics learning activities so students can learn between mathematics and culture, and know the cultural activities that exist in the surrounding community. In this study, the ethnomathematics of the tumpeng and the Tumpeng Sewu Banyuwangi ritual, which is one of the cultures in Indonesia, will be described as well as utilizing the results of their research into ethnomathematic Students’ Worksheets (LKS). Ethnomathematics obtained are activities of counting, counting, and measuring, as well as some mathematical concepts such as algebra, arithmetic, and geometry.